Iron intake and iron deficiency anaemia among young women in Kuala Lumpur - Loh, Su Peng; Khor, Geok Lin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Objective: To assess the prevalence of iron deficiency, anaemia and iron deficiency anaemia (IDA) in women aged 20-40 years and its association with iron intake. Methods: A total of 388 women were recruited from universities and work sites in Kuala Lumpur and its suburbs. The subjects comprised 135 Malays, 130 Chinese and 123 Indians. Dietary intake was estimated using a single 24-hour food recall and a semi-quantitative food frequency questionnaire. Haemoglobin (Hb), haematocrit (hct), mean corpuscular volume (MCV) and serum ferritin were determined. Results: The prevalence of anaemia (Hb <12g/dL) was 20.9%, being highest among the Indians (26.4%) and lowest among the Malays (16.4%). About 10.3% of the women showed iron deficiency anaemia (IDA) (Hb <12g/dL + serum ferritin < 15μg/L + MCV <80fl/). The prevalence of IDA was highest in Indians (18.0%) followed by Chinese (9.9%) and Malays (4.3%). The mean (95%CI) intake of total iron was at 14.4 mg/day (95% CI 13.4, 15.5), amounting to 49.7% of the Malaysian recommended nutrient intake (RNI). Intake of iron was the highest for the Indians (16.0 mg/d) and the lowest for the Chinese (11.3 mg/d). Conclusions: The overall prevalence of IDA was lower compared to prevalence of anaemia. Nonetheless, the markedly higher prevalence of IDA among the Indians, despite relatively higher intake levels of iron-rich foods warrants further investigations, including the bioavailability of iron in the context of cultural practices that may influence food preferences and meal preparation.